FACTORS RELATED TO THE SUCCESS OF DELIVERY ASSISTANCE BY HEALTH PERSONNEL IN LAMPUNG BARAT REGENCY - Kusuma, Anggi (Journals of Ners Community, 2025)
ABSTRACT The Maternal Mortality Rate in Indonesia until 2019 is reported to be still high, namely 305 per 100,000 live births, higher than the target of the Sustainable Development Goals, which is less than 70 per 100,000 KH. The high MMR is closely related to health personnel's achievement of delivery assistance. The higher the achievement of successful delivery by health personnel, the lower the MMR in West Lampung Regency, there was an increase in cases of maternal death in 2019 by 4 cases to 8 cases in 2021; the achievement of delivery assistance by health workers was 93%, with an MMR of 145.6/100,000 KH in 2021, higher than the target of 110/100,000 KH. This study aimed to determine the factors related to the success of delivery assistance by health workers in West Lampung Regency.This study's results indicate a significant correlation between knowledge and facilities/infrastructure with the success of delivery assistance by midwives in West Lampung Regency with a p-value of p=0.000 (<0.05). It is recommended that midwifery health workers increase their knowledge, facilities/infrastructure and attend relevant training and continuous coaching.